Approximate calculation of the potential profile in a graphene‐based device. Issue 1 (1st January 2015) - Marconcini, Paolo; Macucci, Massimo
Abstract : The study of the transport and noise properties of graphene‐based devices requires the computation of the potential profile as a function of the applied bias voltages. However, an exact solution for the potential profile involves a complete self‐consistent treatment of the electrostatic and transport equations, which is computationally very expensive. Here, generalising the approach proposed by Das, et al., the authors describe an approximate method that allows the evaluation of the potential profile by properly modifying, as a function of the bias voltages applied to the gates, the profile for a reference bias point, which is supposed to be known. The proposed approach is not very demanding from the computational point of view and can be useful for simulations aimed at the interpretation of experimental results or at device design.